Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

If $a^3+12ab^2=679$ and $9a^2b+12b^3=978$, find $a^2-4ab+4b^2$.

share|improve this question

closed as off-topic by 900 sit-ups a day, glace, Hakim, RecklessReckoner, Gina Jul 20 at 2:01

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – 900 sit-ups a day, glace, Hakim, RecklessReckoner, Gina
If this question can be reworded to fit the rules in the help center, please edit the question.

    
Hint : $a^2-4ab+4b^2 == (a-2b)^2$. Also take a look at what happens when you sum the first two equations. –  Andrey Nov 19 '12 at 9:35
3  
Hint: The title of the page says "Ask Question" and not "Post a Problem". Questions have question marks. –  Asaf Karagila Nov 19 '12 at 9:38

1 Answer 1

$27(a^3+12ab^2)+18(9a^2b+12b^3)=27(679)+18(978)\implies (3a+6b)^3=33^3 \implies (a+2b)^3=11^3$

Similarly, $-27(a^3+12ab^2)+18(9a^2b+12b^3)=-27(679)+18(978)\implies (-a+2b)^3=(-3)^3$

Following is how $18,27$ are identified as the multipliers.

Clearly, $a\cdot b\ne 0$

$A^3(a^3+12ab^2)=(Aa)^3+3(Aa)(2Ab)^2$ and $18B^3(9a^2b+12b^3)=(6Bb)^3+3(6Bb)(3Ba)^2$

$A^3(a^3+12ab^2)+18B^3(9a^2b+12b^3)=A^3679+18B^3978$

If we put, $x=Aa,y^2=(2Ab)^2$ and $y=6Bb,x^2=(3Ba)^2,$ $A^3(a^3+12ab^2)+18B^3(9a^2b+12b^3)=(x+y)^3$

Comparing the values of $x^2,A^2=9B^2$ which is satisfied by comparing the values of $y^2$

So, $A=\pm 3B, A^3=\pm 27B^3,$

$\pm27B^3(a^3+12ab^2)+18B^3(9a^2b+12b^3)=(x+y)^3$

If $A=3B,$ and $x=Aa=3Ba, \{3B(a +2b)\}^3=(3B)^3679+18B^3978$

This is true for all the values of $B.$

If we take $B\ne 0, (a+2b)^3=1331\implies a+2b=11w_1$ where $w_1$ is a cube root of $1$

Similarly, for $A=-3B, (-a+2b)^3=-27\implies -a+2b=-3w_2$ where $w_2$ is a cube root of $1$

Now solve for $a,b$

share|improve this answer

Not the answer you're looking for? Browse other questions tagged or ask your own question.